2007
DOI: 10.1111/j.1365-2648.2007.04263.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health nurses’ perceptions of their current and future roles

Abstract: Education programmes will need to address specifically the knowledge and skills required for wellness-based models of practice in occupational health nursing, as well as research and negotiating skills for working with others in the workplace.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Our findings are consistent with previous studies [15,17,20,23], with ‘good clinical care’ and ‘communication skills’ being high priorities and ‘research’ a lower priority. In a global survey of OH professionals for OHNs, ‘clinically focused’ competencies were the skills most frequently noted.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings are consistent with previous studies [15,17,20,23], with ‘good clinical care’ and ‘communication skills’ being high priorities and ‘research’ a lower priority. In a global survey of OH professionals for OHNs, ‘clinically focused’ competencies were the skills most frequently noted.…”
Section: Discussionsupporting
confidence: 93%
“…Scores for research were low relative to other OH professionals and few countries identified basic research as part of a nurse’s expected role [15]. In two Australian studies [20,23], OHNs saw ‘traditional role’ (clinically based) activities as more applicable to their practice rather than ‘emergent role’ activities such as health promotion, education and training and research. Our findings also highlight some correlation between OHN and employer perspectives with effective communication also high on employers’ priority lists and research considered least important [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, in retrospect, individually conducted interviews might have been a better methodological strategy to facilitate higher personnel participation and to gain deeper understanding of the personnel's reported experiences and perceptions. Previous studies including participation in health promotion models show an equally low response rate of 22-30% in nursing personnel, but in those studies no explanation was given to this fact [30,31]. Additional limitations included difficulties in identifying the participants on tape which resulted in quotations named from each focus group and not from a certain participant or in relation to the specific type of health promotion intervention the participant had received.…”
Section: Discussionmentioning
confidence: 99%